4D printing and stimuli-responsive materials in biomedical aspects. (1st July 2019) - Lui, Yuan Siang; Sow, Wan Ting; Tan, Lay Poh; Wu, Yunlong; Lai, Yuekun; Li, Huaqiong
Graphical abstract: Abstract: Three-dimensional (3D) printing has revolutionized the world manufacturing production. In biomedical applications, however, 3D printed constructs fell short of expectations mainly due to their inability to adequately mimic the dynamic human tissues. To date, most of the 3D printed biomedical structures are largely static and inanimate as they lack the time-dependant dimension. To adequately address the dynamic healing and regeneration process of human tissues, 4D printing emerges as an important development where "time" is incorporated into the conventional concept of 3D printing as the fourth dimension. As such, additive manufacturing (AM) evolves from 3D to 4D printing and in the process putting stimulus-responsive materials in the limelight. In this review, the state-of-the-art efforts in integrating the time-dependent behaviour of stimulus-responsive materials in 4D printing will be discussed. In addition, current literatures on the interactions between various types of stimuli (categorized under physical, chemical and biological signals) with the associated stimulus-responsive materials will be the major focus in this review. Lastly, potential usage of 4D printing in biomedical applications will also be discussed, followed by technical considerations as well as outlook for future discoveries. Statement of Significance: In this Review, we have demonstrated the significance of 4D printing in biomedical applications, in which "time" has been incorporated into the conventional concept of 3D printing as the 4th dimension. As such, 4D printing differentiates and evolves from 3D printing using stimulus-responsive materials which can actively respond to external stimuli and more sophisticated "hardware"-printer which can achieve multi-printing via mathematical-predicted designs that are programmed to consider the transformation of 3D constructs over time. The emphasize will be on the interactions between various types of stimuli (categorized under physical, chemical and biological signals) with the associated stimulus-responsive materials, followed by technical considerations as well as outlook for future discoveries.